An analysis of publication trajectory in plastic surgery across the decades. Issue 1 (January 2022) - Spake, Carole S.L.; Zeyl, Victoria G.; Crozier, Joseph W.; Rao, Vinay; Kalliainen, Loree K.
Summary: The classic canonical publication trajectory for academicians has been well-described by a rapid increase followed by a slower decrease in productivity, leading to a plateau. This trajectory has not been investigated in plastic surgery. In this communication, we aimed to: (1) visualize the publication trajectory per decade for plastic surgeons certified from 1980 to 2010, and (2) characterize and quantify the changes in publishing trends across decades. A list of plastic and reconstructive surgeons board certified between 1980 and 2010 was obtained. Number of publications per year was recorded for each plastic surgeon. The median cumulative publication trajectory was graphed for each decade. Kruskal-Wallis analysis was performed to determine whether there were differences in number of publications across generations. The trajectory for a surgeon from the 1980s follows the established canonical trajectory. Surgeons from the 1990s and 2000s had significantly more publications by board certification than those from the 1980s (7 and 8 vs. 5, respectively, p  < 0.01). Surgeons from the 2010s on average achieved 8 publications by board certification. It is clear that the publication arc for plastic surgeons from successive generations has greatly changed. Over the last 40 years, there has been a trend for increasing productivity and involvement in research at a much earlier stage in career, potentially due to increasing demands for matching into residency programs.